Relationship between nucleosome positioning and DNA methylation - Chodavarapu, Ramakrishna K.; Feng, Suhua; Bernatavichute, Yana V.; Chen, Pao-Yang; Stroud, Hume; Yu, Yanchun; Hetzel, Jonathan A.; Kuo, Frank; Kim, Jin; Cokus, Shawn J.; Casero, David; Bernal, Maria; et al. (Nature, 2010)
Nucleosomes compact and regulate access to DNA in the nucleus, and are composed of approximately 147 bases of DNA wrapped around a histone octamer. Here we report a genome-wide nucleosome positioning analysis of Arabidopsis thaliana using massively parallel sequencing of mononucleosomes. By combining this data with profiles of DNA methylation at single base resolution, we identified 10-base periodicities in the DNA methylation status of nucleosome-bound DNA and found that nucleosomal DNA was more highly methylated than flanking DNA. These results indicate that nucleosome positioning influences DNA methylation patterning throughout the genome and that DNA methyltransferases preferentially target nucleosome-bound DNA. We also observed similar trends in human nucleosomal DNA, indicating that the relationships between nucleosomes and DNA methyltransferases are conserved. Finally, as has been observed in animals, nucleosomes were highly enriched on exons, and preferentially positioned at intron-exon and exon-intron boundaries. RNA polymerase II (Pol II) was also enriched on exons relative to introns, consistent with the hypothesis that nucleosome positioning regulates Pol II processivity. DNA methylation is also enriched on exons, consistent with the targeting of DNA methylation to nucleosomes, and suggesting a role for DNA methylation in exon definition.
Gesehen am 13.03.2023